Luteolin Attenuates Doxorubicin-Induced Cardiotoxicity Through Promoting Mitochondrial Autophagy - Xu, Haixia; Yu, Wenjun; Sun, Shiqun; Li, Congye; Zhang, Yingmei; Ren, Jun (Frontiers in Physiology, 2020)
Doxorubicin is a valuable antineoplastic drug although its clinical use is greatly hindered by its severe cardiotoxicity with dismal target therapy available. Luteolin is a natural product extracted from vegetables and fruits with a wide range of biological efficacies including anti-oxidative, anti-tumorigenic, and anti-inflammatory properties. This study was designed to examine the possible effect of luteolin on doxorubicin-induced cardiotoxicity, if any, and the mechanism(s) involved with a focus on mitochondrial autophagy. Luteolin application (10 µM) in adult mouse cardiomyocytes overtly improved doxorubicin-induced cardiomyocyte contractile dysfunction including elevated peak shortening amplitude and maximal velocity of shortening/relengthening along with unchanged duration of shortening and relengthening. Luteolin alleviated doxorubicin-induced cardiotoxicity including apoptosis, accumulation of reactive oxygen species (ROS) and loss of mitochondrial membrane potential. Furthermore, luteolin attenuated doxorubicin-induced cardiotoxicity through promoting mitochondrial autophagy in association with facilitating phosphorylation of Drp1 at Ser616, and upregulating TFEB expression. In addition, luteolin treatment partially attenuated low dose doxorubicin-induced elongation of mitochondria. Treatment of Mdivi-1, a Drp1 GTPase inhibitor, negated the protective effect of luteolin on levels of TFEB, LAMP1 and LC3B, as well as loss of mitochondrial membrane potential and cardiomyocyte contractile dysfunction in the face of doxorubicin challenge. Taken together, these findings provide novel insights for the therapeutic efficacy of luteolin against doxorubicin-induced cardiotoxicity possibly through improved mitochondrial autophagy.